Analisis Supply Chain Management (SCM) Menggunakan Metode Value Stream Mapping (VSM) - Audya, Rosa; Bunga Intan; Harma Oktafia Lingga Wijaya (STMIK Budi Darma, 2024)
Micro, Small and Medium Enterprises or commonly called (UMKM) is one of the businesses that can survive during a crisis, one of which is during the economic crisis and food crisis due to the Covid-19 outbreak that occurred in 2020. The activities of umkm have been regulated by the government in Law Number 20 of 2008 concerning micro, small and medium enterprises, Pondok Roti is one of the Micro, Small and Medium Enterprises (Umkm) engaged in the food industry in Lubuklinggau City. This business has been established for 4 years starting in June 2020 until now. Pondok Roti business can produce approximately 670 pieces of bread / day consisting of 11 types of flavors. One method that can be used in Supply Chain Management (SCM), namely the Value Stream Mapping (VSM) method is Value Stream Mapping is a visual method for mapping the production path of a product which includes materials and information from each work station. So, value stream mapping is one of the lean techniques commonly used to analyze the current flow of materials and information needed to bring a product or service to the consumer. The research results of this scientific work are if the PCE (Process Cycle Efficiency) value is less than 30% then it is included in the un-leand, or lean production process. And from the calculation of activities that are NVA (non value added) disebuat waste (waste). From the calculation process that was carried out, the net profit of Pondok Roti in one month was IDR 84,831,200 every month.